Social media in the healthcare context: Ethical challenges and recommendations - Christoffel Grobler; Ames Dhai (South African Journal of Bioethics and Law, 2016)
The popularity of social media has grown rapidly and healthcare practitioners and students commonly use sites such as Facebook. The ethical and professional implications and their benefits and hazards must be considered. Concerns include blurring of boundaries between an individual’s public and professional lives, maintaining privacy and confidentiality of patient information, damaging the public image of the profession and inter-professional relationships. The same laws that apply to conduct in the real world also apply in cyberspace. Harmful or derogatory posts may result in a defamation lawsuit. The internet may also provide opportunities for patient education through peerreviewed websites and to build professional networks. Institutions should have policies on the uses of social media. Emerging technology will continue to change the landscape of social media and social networking and the way patients and practitioners use websites will continue to evolve. Practitioners should proactively manage digital identity by reviewing publicly available material and maintaining strict privacy settings about their information.